Examining social determinants of undiagnosed diabetes in Namibia and South Africa using a behavioral model of health services use. (May 2021) - Lee, Shinduk; Washburn, David J.; Colwell, Brian; Gwarzo, Ibrahim H.; Kellstedt, Debra; Ahenda, Petronella; Maddock, Jay E.
Abstract: Aims: To examine factors associated with undiagnosed diabetes in Namibia and South Africa. Methods: This study used the most recent Demographic and Health Surveys (DHS) from Namibia (2013) and South Africa (2016). This study focused on adults at 35–64 years old. Using Andersen's Behavioral Model, potential contributing factors were categorized into predisposing factors (sex and education), enabling factors (wealth, health insurance, and residence), and a need factor (age, BMI, and high blood pressure). Separate multivariable logistic regression models were used to examine factors associated with undiagnosed diabetes in Namibia (N = 242) and South Africa (N = 525). Results: In Namibia, higher odds of having undiagnosed diabetes were associated with rural residence (adjusted odds ratio (aOR) = 2.21) and age younger than 45 years old (aOR = 3.20). In South Africa, odds of having undiagnosed diabetes were higher among the poorest-to-poorer group than it was in the richer-to-richest group (aOR = 2.33). In both countries, having high blood pressure was associated with lower odds of having undiagnosed diabetes (aOR = 0.31 in Namibia; aOR = 0.21 in South Africa). Discussion: Different enabling and need factors were associated with undiagnosed diabetes in these two countries, which implies potentially-different mechanisms driving the high prevalence of undiagnosed diabetes, as well as the needs for different solutions.